Loose-Leaf Lettuce genotypes for the Agreste region in Sergipe, Brazil - Souza, Juliana Lopes; Silva, Susi Alves da; Silva-Mann, Renata; Gonçalves, Gláucia Barretto; Gomes, Luiz Antônio Augusto; Carvalho Filho, José Luiz Sandes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Among the leafy vegetables, lettuce is one of the most consumed in Brazil, being recommended the use of cultivars adapted to different climatic conditions. Therefore, this work had the objective to select lettuce genotypes of smooth leaves and tolerant to the early flowering. The experiment was carried out in the city of Itabaiana, State of Sergipe in experimental design of randomized blocks with three replications. Twelve genotypes were evaluated for fresh and dry weight of shoot, fresh and dry mass of root, mass and number of commercial and non-commercial leaves, head diameter and stem length. The genotype AFX005B-121-02, which has smooth leaves and is bolting tolerant, presented better agronomical and commercial performance, being promising for cultivation conditions in the Agreste region.